2021
DOI: 10.1177/1759720x211002593
|View full text |Cite
|
Sign up to set email alerts
|

Early anti IL-1 treatment replaces steroids in refractory Kawasaki disease: clinical experience from two case reports

Abstract: Refractory Kawasaki disease (KD) is related to a major risk of coronary arteries abnormalities and its treatment is not standardized. In this regard, anakinra (ANA), an interleukin (IL)-1 receptor antagonist, represents an emerging therapeutic option. We report two cases of children, diagnosed with KD, nonresponsive to two doses of intravenous immunoglobulins, successfully treated with ANA, without a prior use of steroids. Patient 2 developed a coronary dilatation, that improved significantly after ANA therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(78 reference statements)
0
1
0
1
Order By: Relevance
“…Болезнь Кавасаки Ретроспективное исследование, клинические наблюдения [226][227][228][229][230][231][232][233][234][235][236][237][238] Вторичный синдром активации макрофагов/ГЛГ при ИВЗ Клинические наблюдения [239][240][241][242][243][244] COVID-19 ассоциированный гипервоспалительный синдром РПКИ (CORIMUNO, SAVE-MORE) [245,246], наблюдательные исследования [247][248][249][250][251][252][253][254], метаанализы [255,256]…”
Section: гипервоспалительные синдромыunclassified
“…Болезнь Кавасаки Ретроспективное исследование, клинические наблюдения [226][227][228][229][230][231][232][233][234][235][236][237][238] Вторичный синдром активации макрофагов/ГЛГ при ИВЗ Клинические наблюдения [239][240][241][242][243][244] COVID-19 ассоциированный гипервоспалительный синдром РПКИ (CORIMUNO, SAVE-MORE) [245,246], наблюдательные исследования [247][248][249][250][251][252][253][254], метаанализы [255,256]…”
Section: гипервоспалительные синдромыunclassified
“…Authors concluded that anakinra may be considered as an option after the failure of the first IVIG infusion, especially in patients with coronary involvement ( 90 ). Mastrolia MV et al have recently reported two cases of children, diagnosed with KD, non-responsive to two doses of intravenous immunoglobulins, successfully treated with ANA, without prior use of steroids ( 91 ). Further studies are planned/ongoing to reveal its clinical significance (ANACOMP, ANAKID) and to better define the place of IL-1 blockade in KD step-up treatment.…”
Section: Second-line Treatmentmentioning
confidence: 99%